CRITICAL SUCCESS FACTOR OF PRIVATIZATION PROJECT - Ismail, Azizah; Nadzri Jaafar, Mohd; Abdullah, Mat Naim; Asmoni, Mohd; Abdullah, Musyirah (Journal of Sustainable Technology and Applied Science (JSTAS), 2020)
Privatization is generally defined as the transfer of activity and function, particularly in the area of infrastructure development for the purpose of improving management efficiency, productivity as well as ensuring economic growth in tandem with the vision 2020. Although the privatization of certain property development projects has been successfully implemented, there are still a number of abandoned projects and the reasons for success are not fully explained. In Johor, there has been no study on the success factors of the privatization project for commercial buildings. Therefore, the objective of this study is to define critical success factors for privatized development projects and to identify developers' characteristics that affect the success factor of a privatization project by identify the successful privatization projects and selected 3 successful privatized commercial privatization projects. Furthermore, the characteristics of developers affecting the success of the project will be identified to facilitate the Johor State Economic Planning Division to identify the criteria of the developer to the project which has the potential of a successful privatization project.